Hörspiel et musique autour de 1960 : l’exemple du Hörspiel de Dieter Wellershoff, Am ungenauen Ort - Adina Toma (Tr@jectoires)
The importance and uses of music in the Hörspiele, a hybrid genre that is constantly being redefined, have fluctuated from the moment it originated to the present day. In West Germany, the aesthetics of this radio genre focused on verbal language after the Second World War and evolved until a paradigm shift at the end of the 1960s with the Neues Hörspiel, which placed music and non-verbal sound experimentation at the centre of its dramaturgy and turned the manuscript into a score. Beyond these schematic categories of the history of the Hörspiel, the article examines the increasingly important and diverse use of music around 1960, based on the example of a work by Dieter Wellershoff, Am ungenauen Ort (1960, SDR), in which the use of music and musicalisation respond to the theme of the difficulty of language and dialogue.